2016
DOI: 10.1515/bnm-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Degradation rates and products of pure magnesium exposed to different aqueous media under physiological conditions

Abstract: As magnesium and many of its alloys are a promising class of degradable implant materials, a thorough understanding of their degradation under physiological conditions is a key challenge in the field of biomaterial science. In order to increase the predictive power of in vitro studies, it is necessary to imitate the in vivo conditions, track the decomposition process and identify the products that form during the degradation pathway. In this in vitro study, slices of pure magnesium were exposed to Hank’s Balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Also in addition to results shown in Ref. we have observed Fe, Si, Nd, Mn, and Zn signals. These are expected to be artefacts from material production and handling, as none of these elements are contained in the culture medium.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Also in addition to results shown in Ref. we have observed Fe, Si, Nd, Mn, and Zn signals. These are expected to be artefacts from material production and handling, as none of these elements are contained in the culture medium.…”
Section: Discussionsupporting
confidence: 87%
“…As regions of P and Ca overlap (Figure C) the formation of hydroxyapatite is likely, which is supported by its high dissolution constant stated in Ref. . Further formation of calcite CaCO 3 and portlandite Ca(OH) 2 cannot be distinguished with the current measurements, due to technical limitations.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The corrosion rates for Mg may differ depending on various parameters: the degree of its purity, heat treatment of the material, the type of electrolyte, the time of immersion, the crystal orientation, etc. [6,7,17,[26][27][28][29][30][31]. As reported, Mg in the high-purity form has the lowest corrosion rate, below 1 mlcm −2 day −1 .…”
Section: Evolution Of the Corrosion Reaction With Timementioning
confidence: 61%
“…The dimensions of the scales on the other samples are somewhat smaller, but are roughly of the same order of magnitude; thus, it can be tentatively concluded that thicknesses of the degradation layers are 10-100 µm. The surface morphology is typical of Mg alloys exposed to buffered SBF, e.g., [26,27]. SEM imaging of the surface was also attempted but, due to the strong charging of the surface, only two poor-quality SEM images were obtained, with brightness over-saturation on the upper surfaces ( Figure 6).…”
Section: Xps Of Samples After Sbf Immersionmentioning
confidence: 99%